Morphological and genetic diversity of Beaufort Sea diatoms with high contributions from the Chaetoceros neogracilis species complex. Issue 1 (5th December 2016) - Balzano, Sergio; Percopo, Isabella; Siano, Raffaele; Gourvil, Priscillia; Chanoine, Mélanie; Marie, Dominique; Vaulot, Daniel; Sarno, Diana
Abstract : Seventy‐five diatom strains isolated from the Beaufort Sea (Canadian Arctic) in the summer of 2009 were characterized by light and electron microscopy (SEM and TEM), as well as 18S and 28S rRNA gene sequencing. These strains group into 20 genotypes and 17 morphotypes and are affiliated with the genera Arcocellulus, Attheya, Chaetoceros, Cylindrotheca, Eucampia, Nitzschia, Porosira, Pseudo‐nitzschia, Shionodiscus, Thalassiosira, and Synedropsis . Most of the species have a distribution confined to the northern/polar area. Chaetoceros neogracilis and Chaetoceros gelidus were the most represented taxa. Strains of C. neogracilis were morphologically similar and shared identical 18S rRNA gene sequences, but belonged to four distinct genetic clades based on 28S rRNA, ITS‐1 and ITS‐2 phylogenies. Secondary structure prediction revealed that these four clades differ in hemi‐compensatory base changes (HCBCs) in paired positions of the ITS‐2, suggesting their inability to interbreed. Reproductively isolated C. neogracilis genotypes can thus co‐occur in summer phytoplankton communities in the Beaufort Sea. C. neogracilis generally occurred as single cells but also formed short colonies. It is phylogenetically distinct from an Antarctic species, erroneously identified in some previous studies as C. neogracilis, but named here as Chaetoceros sp. This work provides taxonomically validated sequences for 20 Arctic diatom taxa, which will facilitate future metabarcoding studies on phytoplankton in this region.